Experimental investigation and thermodynamic assessment of phase equilibria in the Cr-Re-Ru ternary system. (September 2021) - Wang, C.P.; Ren, H.; Liu, H.; Li, L.L.; Yang, S.Y.; Han, J.J.; Lu, Y.; Guo, Y.H.; Huang, Y.X.; Liu, X.J.
Abstract: The phase equilibria of the Cr-Re-Ru ternary system at 1100 °C and 1200 °C have been experimentally investigated using electron probe microanalyzer and X-ray diffraction. The σ1 -Cr2 Re3 and σ2 -Cr2 Ru phases with the same D8b crystal structure do not form a continuous intermetallic compound phase at 1100 °C and 1200 °C in the Cr-Re-Ru ternary system confirmed by experimental results. According to the experimental results in this work, the Cr-Re-Ru ternary system has been assessed by means of the CALPHAD (CALculation of PHAse Diagrams) method. The calculated isothermal section at 1400 °C shows that the two independent phases σ1 -Cr2 Re3 and σ2 -Cr2 Ru are replaced by the continuous intermetallic compound σ. The current established thermodynamic database of the Cr-Re-Ru ternary system may provide the essential information, and support for the thermodynamic assessment of multicomponent system and the development of Ni-based superalloys.